NATO-Kazakhstan cooperation within the Partnership for Peace programme: lessons and perspectives of further development (International relations and international law Journal, 2016)
This article focuses on relationship between NATO and Kazakhstan. This article examines the Alliance’s partnership policy in Central Asia and aims to clarify to what extent NATO’s new partnership policy can affect its relations with these countries. This article reviews lessons learned after 20 years of cooperation between NATO and Kazakhstan within the PfP programme and discusses the role of NATO’s PfP program in shaping Central Asian security architecture. The author determines that learning the lessons and best practices of Pfp Programme after 20 years will allow to prepare practical recommendations for government agencies of Central Asian countries on enhancing cooperation with NATO within the framework of the PfP Programme in order to strengthen security and cooperation in the Euro-Atlantic and Central Asian region.
Keywords: NATO; NATO’s partnership policy; Central Asia; Kazakhstan; PfP